GPCR19 Regulates P2X7R-Mediated NLRP3 Inflammasomal Activation of Microglia by Amyloid β in a Mouse Model of Alzheimer’s Disease - Islam, Jahirul; Cho, Jung-Ah; Kim, Ju-yong; Park, Kyung-Sun; Koh, Young-Jae; Chung, Chu Young; Lee, Eun-Jae; Nam, Soo Jeong; Lee, Kyoungyul; Kim, Seoung-Heon; Park, Sung-Hye; Lee, Dong Young; et al. (Frontiers in Immunology, 2022)
Amyloid β (Aβ) and/or ATP activate the NLRP3 inflammasome (N3I) via P2X7R in microglia, which is crucial in neuroinflammation in Alzheimer’s disease (AD). Due to polymorphisms, subtypes, and ubiquitous expression of P2X7R, inhibition of P2X7R has not been effective for AD. We first report that taurodeoxycholate (TDCA), a GPCR19 ligand, inhibited the priming phase of N3I activation, suppressed P2X7R expression and P2X7R-mediated Ca++ mobilization and N3I oligomerization, which is essential for production of IL-1β/IL-18 by microglia. Furthermore, TDCA enhanced phagocytosis of Aβ and decreased the number of Aβ plaques in the brains of 5x Familial Alzheimer’s disease (5xFAD) mice. TDCA also reduced microgliosis, prevented neuronal loss, and improved memory function in 5xFAD mice. The pleiotropic roles of GPCR19 in P2X7R-mediated N3I activation suggest that targeting GPCR19 might resolve neuroinflammation in AD patients.